(untitled) (Transport systems and technologies, 2022)
The article considers the problems of energy efficiency management of the rolling stock of the transport sector. The operation and operation of vehicles are analyzed and it is determined that road transport is the main consumer of energy resources in the transport sector, which is about 90%. Road transport requires 6.5 times more fuel than rail, and 5 times more fuel than sea or river. It has been studied that the transport sector has a negative impact on environmental friendliness due to high emissions. To successfully solve this problem, it is necessary to use bioenergy, which will increase the energy efficiency and environmental friendliness of the transport sector and is a strategy for the development of the transport sector of the country and the European Union. An analytical review of legislative acts, namely EU directives and national transport strategy for the period up to 2030, which regulate the promotion of energy efficiency in transport. The main groups of tools and the use of information technology are considered, which allow to achieve the set goals in the development of energy efficiency in transport. The impact of alternative fuels resulting from the processing of biological waste or biological raw materials for the country’s transport sector, in particular road transport, which will significantly reduce CO2 emissions, has been studied. Biofuels are able to provide clean energy for all modes of transport and are currently the most important type of alternative fuel. Its influence on improving the energy efficiency and environmental friendliness of the transport sector has been studied.